2022
DOI: 10.1155/2022/3618002
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the Nutritional and Taste Characteristics of 5 Edible Fungus Powders Based on the Composition of Hydrolyzed Amino Acids and Free Amino Acids

Abstract: The nutritional characteristics and taste of some edible fungus powders were scientifically evaluated and compared. Five common edible fungus powders were used as test materials (Agrocybe chaxinggu edible fungus powder, Pleurotus citrinopileatus edible fungus powder, Flammulina velutipes edible fungus powder, Lentinus edodes edible fungus powder, and Hericium erinaceus edible fungus powder). The hydrolyzed amino acid and free amino acid content were measured by an automatic amino acid analyzer, and the ratios … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 31 publications
0
9
0
Order By: Relevance
“…Popular edible mushroom species such as Lentinus edodes , Agaricus spp., and Pleurotus spp. contained 14.87 to 27.13% [ 18 ], 26.60 to 39.84% [ 6 ], and 18 to 19.15 g/100 of protein [ 19 ], respectively. Crude protein ranged from 6.60 to 30.69 g/100 g among mushrooms obtained from the Kilum-Ijim forest in Cameroon [ 7 ].…”
Section: Nutritional Value Of Edible Mushroom Proteinsmentioning
confidence: 99%
See 1 more Smart Citation
“…Popular edible mushroom species such as Lentinus edodes , Agaricus spp., and Pleurotus spp. contained 14.87 to 27.13% [ 18 ], 26.60 to 39.84% [ 6 ], and 18 to 19.15 g/100 of protein [ 19 ], respectively. Crude protein ranged from 6.60 to 30.69 g/100 g among mushrooms obtained from the Kilum-Ijim forest in Cameroon [ 7 ].…”
Section: Nutritional Value Of Edible Mushroom Proteinsmentioning
confidence: 99%
“…A recent study found that the value of EAA/ (EAA + NEAA) among the five types of edible fungus studied ranged from 32.20 to 41.87%, and the value of EAA/NEAA was 47.48 to 72.03%. EAA/ (EAA + NEAA) and EAA/NEAA values were lowest in Lentinus edodes but Pleurotus citrinopileatus best fulfilled the optimal protein standard [ 18 ]. In all, the above data point to the fact that mushroom proteins have a complete essential amino acid profile, though the amount varied by variety of factors such as species, production, and processing conditions, but cannot be generalized.…”
Section: Quality Of Mushroom Proteinmentioning
confidence: 99%
“…Crude protein content was determined using the Kjeldahl method (GB5009-2010, semimicro Kjeldahl method); crude fat was determined using the Soxhlet extraction method (GB5009. ; crude ash was determined by cauterized mass method (GB5009.4-2010, cauterized at 550 °in a mufe furnace); crude moisture was determined by drying (GB5009.3-2010, 105 °C drying method); free amino acids were assessed using phenyl isothiocyanate derivatization-high performance liquid chromatography [20]. Fatty acids were determined using the GB/T5009.168-2016 method.…”
Section: Nutrient Compositionmentioning
confidence: 99%
“…Glutamic acid (Glu) and aspartic acid (Asp) are the basic components of umami taste, which makes edible fungi a unique taste (Lü et al, 2022). Li, Ma et al (2022) measured the content of hydrolyzed and free amino acids in five edible fungus' powders and calculated the taste activity value (TAV) of free amino acids that produce taste to evaluate the taste characteristics of each taste amino acid, they found that the most significant influence on the TAV value was Glu. Yang et al (2022) analyzed the taste and flavor changes before and after the addition of three edible funguses to chicken soup and found that the characteristic taste amino acids and flavor components in chicken soup increased after the addition of edible mushrooms.…”
Section: Introductionmentioning
confidence: 99%
“…Li, Ma et al. (2022) measured the content of hydrolyzed and free amino acids in five edible fungus’ powders and calculated the taste activity value (TAV) of free amino acids that produce taste to evaluate the taste characteristics of each taste amino acid, they found that the most significant influence on the TAV value was Glu. Yang et al.…”
Section: Introductionmentioning
confidence: 99%